FRAGMENTS OF THE THIRD MILLENNIUM BC FROM NIGIN. (December 2021) - Nadali, Davide; Verderame, Lorenzo
Abstract : The ancient city of Nigin in the State of Lagash is largely attested in the epigraphic sources of the rulers of the First Dynasty of Lagash. Conversely, the archaeological evidence of the Early Dynastic Period is so far very scanty and limited. This paper presents a small group of documents to be dated to the Early Dynastic Period IIIb that were found out of context, but that nevertheless point to a phase of occupation of Nigin in the third millennium BC and are coherent with the information we already know about history of the city and the State of Lagash.